Crop Varietal Mixtures as a Strategy to Support Insect Pest Control, Yield, Economic, and Nutritional Services - Snyder, Lauren D.; Gómez, Miguel I.; Power, Alison G. (Frontiers in Sustainable Food Systems, 2020)
Most on-farm diversification strategies to enhance ecosystem services, such as insect pest control and yield, have focused on expanding crop species diversity. While polycultures often provide valuable services, logistical constraints with planting and harvesting can hamper implementation on large scales. An alternative diversification strategy is to increase within-field intraspecific crop diversity through the use of crop varietal mixtures. Here, we evaluate an interdisciplinary body of research to determine the potential for crop varietal mixtures to support food security by providing ecological, economic, and nutritional services. Previous literature has synthesized the link between varietal mixtures and yield and insect pest suppression services. We expand on prior analyses by considering hypotheses generated from species-level research and assessing whether they also provide a useful framework for predicting how varietal mixtures affect crop productivity and insect pest suppression. In addition, we evaluate the potential for varietal mixtures to increase farm resilience and growers' profits. While there is a growing effort to quantify the economic value of ecosystem services provided by agrobiodiversity in terms of enhanced yield or revenue, much less attention has been given to quantifying the production costs associated with diversification schemes. Consequently, we know little about the effect of diversification practices on farm profitability, the metric of ultimate importance to farmers. We address this issue by evaluating the ability of varietal mixtures to reduce production costs associated with other types of agrobiodiversity and outline areas for future research to better understand the profit implications of varietal mixtures. Further, we review evidence that varieties of some crop species differ in phytochemical content—a functional trait important for insect pest suppression and human dietary diversity—suggesting that varietal mixtures could be designed to simultaneously support insect pest control and human nutrition services. Given that little research has explicitly addressed the capacity for varietal mixtures to support human nutrition, we outline predictions for where we would expect to see the greatest nutritional impact of mixtures, providing a foundation for future human nutrition research. Taken together, our review suggests that varietal mixtures are a promising and logistically feasible strategy that could simultaneously support multiple services.